Percayaan Diri, Religiusitas dan Perilaku Menyontek - Evi Kusdiana; M. As’ad Djalali; M. Farid (JKI (Jurnal Konseling Indonesia), 2018)
The cheating on exam attitude is a dishonest attitude. It can be done through copying, imitating, quoting, or duplicating the other student’s essay/work to take the advantage in answering the questions of the exam.The aim of the research is to find out the correlation between self – confidence and religiousity toward the cheating on exam. The test of the instrument on the cheating attitude scale gives a result on 46 valid and reliable items. The subject of the research is 87 students by the technique of multistage cluster sampling. The data analysis technique used in the research is the double regression statistical analysis to examine the correlation between self-confidence and religousity with the cheating attitude, and the partial correlation technique to examine each independent variable toward the dependent one. Based on the calculation result using the regression statistical test, it shows that there is a negative correlation between self-confidence and religousity with the cheating attitude of the junior high school students (F= 20,398 and p = 0,000 : p < 0, 001). There is a significantly negative correlation between self-confidence and religousity with the cheating attitude (p = 0,024 ; p < 0,05). There is a very significantly negative correlation between religousity and the cheating attitude (p = 0,000 ; p < 0,01).